HIDUP BERDAMPINGAN DALAM PERBEDAAN: STUDI TOLERANSI NU, MUHAMMADIYAH, DAN SERIKAT ISLAM DI DESA HARUMANSARI - Fathurrahman, Aceng; Putri Ramadhina, Aurelia; Karomah, Fitri (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program was carried out in Harumansari Village, Kadungora District, Garut Regency, which is characterized by the coexistence of three major Islamic organizations: Nahdlatul Ulama (NU), Muhammadiyah, and Serikat Islam (SI). Although these organizations differ in religious traditions, preaching methods, and social orientations, the community has shown the ability to maintain harmony. The purpose of this program was to analyze how tolerance is practiced, identify the factors that support and hinder it, and design strategies to strengthen peaceful coexistence. The study employed a qualitative descriptive method with a case study approach, using participatory observation, in-depth interviews, and documentation. The results revealed that tolerance was successfully manifested through mutual respect in worship, social collaboration across organizations, joint participation in religious activities, and inclusive dialogue in village forums. Local cultural values such as silih asih, silih asah, and silih asuh became key instruments in maintaining social harmony. The program concluded that small-scale tensions, in line with Lewis A. Coser’s conflict theory, played a positive role in reinforcing solidarity and adaptive social mechanisms. The success of this program lies in strengthening communication, fostering inclusive leadership, and building a replicable grassroots model of religious tolerance for other communities in Indonesia.